Local urban warming, possible impacts and a resilience plan to climate change for the historical center of Athens, Greece. (December 2015) - Santamouris, Matheos; Cartalis, Constantinos; Synnefa, A.
Highlights: We examine local urban warming in Athens, with emphasis to the historical center. We examine and quantify to the extent possible, the impacts to environment, energy, health and the economy. We review mitigation and adaption measures for urban climate change. We develop a resilience plan for urban climate change for the historic center of Athens. Abstract: Urban climatic change poses a threat to the built environment and urban landscapes, especially those of historical importance which are considered particularly vulnerable. In Athens, Greece, the degradation of the thermal environment may endanger landscapes and buildings within the historic center of the city. In this paper, the impact of the urban heat island to the prevailing environmental and microclimatic conditions, to the needs for energy production and use at the city and neighborhoods, and to the society, especially with respect to the quality of life, the exposure of elderly people to adverse thermal conditions and to the capacity of households to adjust are provided and discussed in detail. The plan attempts to integrate climate change factors in the management of the building stock and of the landscape, in the historic center of the city.